Response Surface Method for the Simultaneous Estimation of Atorvastatin and Olmesartan - Dandamudi, Santhoshi Priya; Chettupalli, Ananda Kumar; Dargakrishna, Shanthi Priya; Nerella, Mounika; Amara, Ramkoteswar Rao; Yata, Vinod Kumar (Trends in Sciences, 2022)
The simultaneous estimation of Atorvastatin Calcium (ATS) and Olmesartan Medoxomil (OLM) in bulk and pharmaceutical dosage forms, a new, quick, and cost-effective Reverse Phase High Performance Liquid Chromatography (RP-HPLC) method has been developed. The experimental design was used to achieve multivariate optimization of the RP-HPLC experimental conditions. Three independent variables were used to create mathematical models: Acetonitrile content in the mobile phase composition, buffer pH, and flow rate. Here, the applied model was central composite design (CCD) to research the response surface methodology and study the effects of independent factors. The Shimadzu (LC 20 AT VP) HPLC system with Spinchrom software has been used. Zodiac, C18 (250×4.6 ID) 5μm column, phosphate buffers, and acetonitrile were used as mobile phase in the ratio 40:60 v/v with a flow rate 1.15 mL/min. The eluent was monitored at 212 nm using the Prominence UV-Visible detector. The retention time for OLM and ATS was 2.673 and 3.717, respectively. The optimized procedure was validated as per ICH guidelines. The correlation coefficient of OLM and ATS was 0.9869 and 0.9832. The % of recovery was 98.59, 99.68 %. OLM had a LOD of 17.568 μg/mL, while ATS had a LOD of 12.88 μg/mL. OLM had a LOQ of 53.24 μg/mL, while ATS had a LOQ of 39.04 μg/mL. The pH aqueous phase, solvent composition, and flow rate were the most stringent variables affecting the responses, according to the 3D response surface graphs. A new accurate and precise RP-HPLC approach has been developed and validated and used to regularly analyse OLM and ATS. HIGHLIGHTS A new, quick, and cost-effective RP-HPLC method for the simultaneous estimation of Atorvastatin Calcium and Olmesartan Medoxomil in bulk and pharmaceutical dosage forms RP-HPLC method developed by experimental design and response surface method Developed method was validated as per ICH guidelines GRAPHICAL ABSTRACT